ANALISIS KELAYAKAN FINANSIAL AGROWISATA KEBUN BUAH (Studi Kasus di Agrowisata Kebun Buah Mangunan, Bantul, Yogyakarta) - Anisa Tri Sofiana (Fakultas Pertanian UST, 2017)
This research aims to determine the advantages of Mangunan orchard, to determine the financial feasibility which is based on the investment criteria, and to determine the time period of investment return of Mangunan orchard agro-tourism based on the costs incurred and benefits. The data of this research are analyzed by using the investment analysis through NPV, BCR, IRR, and Payback Period analysis. The NPC, BCR, and IRR analysis refer to the financial viability and profitability while the Payback Period emphasizes the time period of investment return. The result of this research shows that Mangunan orchard agro-tourism is feasible because it can benefit. From the financial analysis on the interest rate of 12%, it gets the NPV in the amount of Rp. 50.707.576.366 which indicates the profit in amount of Rp. 50.707.576.366 during the life of the project. The BCR analysis obtains a value of 3,68 which indicates that for every Rp. 1 costs incurred will give benefit in amount of 3,68. In addition, the IRR analysis obtains a value in amount of 18,92 % which shows that there will be a payback when the interest rate reaches 18,92 %. Based on the criteria of return on investment (payback period) from the calculations, it obtains that the payback period around 14 years and 9 moths, which means in the time period, the investment costs incurred can be returned.Â Key words: Mangunan Orchard Agro-tourism, Feasibility.